Management of Grants in The World of Education - Amiruddin Siahaan; Nurika Khalila Daulay; Suriadi Panjaitan; Mayasari Mayasari; Mukthi Halwi (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2022)
Grants are the provision of money/goods or services from the regional government to other governments, regional companies, the community, and community organizations, whose designations have specifically been determined, are not mandatory and are not binding, and are not continuously aimed at supporting the administration of business affairs. government, or support the achievement of program targets and local government activities in mandatory and optional affairs. While the source of grant funds itself comes from the source of grants. Grants to local governments can be sourced from: a. Government; b. Other local governments; c. Domestic private agency/institution/organization; and D. Domestic community groups/individuals. Grants from the Government can be sourced from: a. APBN revenue; b. Foreign Loans; and/or c. Foreign Grants. Grants from Foreign Loans and Foreign Grants can be sourced from foreign government governments, foreign agencies/institutions, international agencies/institutions, and/or other donors. Grant funds can be a useful additional resource for educational purposes. District/city schools and schools are advised to develop skills in seeking and obtaining grants. But caution is needed so that grant applications are made wisely and strategically. Grants also have obligations to their recipients and these should be considered before applying. The best approach to establishing the grant-seeking process is to ensure that the grant program considered aligns with and supports the school's strategy or school district plan.